Better Understanding the Workers' Retirement Decision Attitudes: Development and Validation of a New Measure - Fouquereau, Evelyne; Bosselut, Grégoire; Chevalier, Séverine; Coillot, Hélène; Demulier, Virginie; Becker, Caroline; Gillet, Nicolas (Frontiers in Psychology, 2018)
The aim of the present research was to develop a measure that could be used in future research for in-depth study of the psychological management of retirement. We report the results of six studies involving 1,898 French workers designed to develop and assess the psychometric properties of a new instrument named the Workers' Retirement Motivations Inventory (WRMI) using the push pull anti-push anti-pull model. The items were constructed based on a review of the relevant psychological literature and face-to-face interviews with senior workers. A combined method of exploratory structural equations modeling and confirmatory factor analysis was employed and provided evidence for validating this structure of the inventory. The WRMI showed consistency of the four-factor structure across different samples, internal consistency, test-retest reliability and predictive validity of workers' plans for retirement. Implications of these findings and avenues for counseling activities and future research are discussed.